Analysis on the foreign direct investment, economic growth, and economic development in Chad - Gueme, Ganama Moustapha (2022)
Economic development has become the central focus of the development agenda in many developing countries. Despite the increasing number of research conducted in economic development, little has been done to the impact of economic growth and foreign direct investment (FDI) from Sub-Sahara African (SSA) countries, especially in Chad. However, the economic instability and fluctuation in FDI has resulted in low human development, high unemployment, and a low standard of living over the years. Despite the improvement in economic growth in Chad and the amount of FDI the country has received, economic development is still not satisfactory, especially with regards to human development, unemployment levels, and standard of living. Therefore, the aim of this study is to investigate the impact of economic growth and FDI on economic development in the context of Chad. The study collected a sample of time series data from 1980 to 2019 from the World Bank and the national statistical database of Chad. Hence, data were analyzed using the autoregressive distributed lag techniques (ARDL, and NARDL), along with pairwise Granger causality test. The results suggest that economic growth significantly influences economic development in the long-run and short-run. In contrast, FDI has only a partially significant impact on economic development. Additionally, economic growth only Granger-caused the standard of living dimension, while the other two dimensions show no evidence of causality from economic growth to economic development. Also, no Granger causality evidence was found from FDI to economic development. The results from the NARDL further confirm the symmetric effect between GDP growth, FDI and economic development in Chad. This study is beneficial to the government authorities and policymakers of Chad, international organizations, and the extant literature on FDI, economic growth and development. Thus, it is highly recommended that the Chadian government structure a strong government intervention in social sectors such as education, health, and improved standard of living by creating more job opportunities in order to strengthen the overall economic development of the country